Structure and deformational history of the Hawasina Complex in the Sufrat ad Dawh Range, western foothills of the Oman Mountains, Eastern Arabian Peninsula - Barrette, Paul Dominique (1985)
Thesis (M.Sc.)--Memorial University of Newfoundland, 1985. Earth Sciences Bibliography: leaves 135-139.